THE EFFECTIVENESS USING PICTURE AND PICTURE MEDIA TO SOLVE SENIOR HIGH SCHOOL PROBLEM IN WRITING SKILL OF NARRATIVE TEXT AT 10TH GRADE SMAN 1 PEMATANG SIANTAR - RUTH WIDYA PUTRI SIMORANGKIR; SARAH MERRY NATALIA SIMAMORA; LYDIA STEFANI MANURUNG; DEPI LIDIA SIMBOLON; SELVIANA NAPITUPULU (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
The main issues of this research is how to solve problem in writing skill of senior hight school through picture ang picture method. The objective of the research are as follows; (1). To solve student in limited knowledge of Grammar and Vocabulary, (2) to develop the student ideas in writing skill. The methods/approaches used in achieving the following objectives; (a). its can motivate the student to write correctly. (b). its can stimulate and possible to guide written description. (c). it can help the student to provide information to be referred to in discussion or storytelling. Research subject is the students of tenth grade in Senior High School 1 Pematangsiantar. Base on the result the researcher can conclude that using picture and picture method can solve problem writing skill of Senior Hight School’s student